HMGB1 coordinates SASP‐related chromatin folding and RNA homeostasis on the path to senescence - Konstantinos Sofiadis; Natasa Josipovic; Milos Nikolic; Yulia Kargapolova; Nadine Übelmesser; Vassiliki Varamogianni‐Mamatsi; Anne Zirkel; Ioanna Papadionysiou; Gary Loughran; James Keane; Audrey Michel; Eduardo G Gusmao; et al. (Molecular Systems Biology)
Abstract Spatial organization and gene expression of mammalian chromosomes are maintained and regulated in conjunction with cell cycle progression. This is perturbed once cells enter senescence and the highly abundant HMGB1 protein is depleted from nuclei to act as an extracellular proinflammatory stimulus. Despite its physiological importance, we know little about the positioning of HMGB1 on chromatin and its nuclear roles. To address this, we mapped HMGB1 binding genome‐wide in two primary cell lines. We integrated ChIP‐seq and Hi‐C with graph theory to uncover clustering of HMGB1‐marked topological domains that harbor genes involved in paracrine senescence. Using simplified Cross‐Linking and Immuno‐Precipitation and functional tests, we show that HMGB1 is also a bona fide RNA‐binding protein (RBP) binding hundreds of mRNAs. It presents an interactome rich in RBPs implicated in senescence regulation. The mRNAs of many of these RBPs are directly bound by HMGB1 and regulate availability of SASP‐relevant transcripts. Our findings reveal a broader than hitherto assumed role for HMGB1 in coordinating chromatin folding and RNA homeostasis as part of a regulatory loop controlling cell‐autonomous and paracrine senescence.